2021
DOI: 10.3389/fpsyg.2021.696891
|View full text |Cite
|
Sign up to set email alerts
|

Towards Better Understanding of the Harmful Impact of Hindrance and Challenge Stressors on Job Burnout of Nurses. A One-Year Cross-Lagged Study on Mediation Role of Work-Family Conflict

Abstract: The mediation role of work–family conflict (WFC) in job demands – job burnout link is well documented, also in group of nurses. It is still unclear, however, which job demands are particularly conducive to WFC and job burnout. Moreover the mediational effect of WFC was tested mainly in cross-sectional studies that were conducted in countries of North America and Western Europe. Drawing on the Job Demands-Resources and the Effort-Recovery models, this one-year cross-lagged study investigates the effects of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…However, we have reached a consensus on the negative impact of hindrance stressors on innovation performance ( Baer et al, 2003 ; Ohly et al, 2006 ; Lin et al, 2015 ). Therefore, we set off from the conservation of resource theory, taking challenge stressors as a positive situation feature and hindrance stressors as a negative situation feature ( Baka and Prusik, 2021 ; Tong et al, 2021 ). At the same time, positive emotional atmosphere and negative emotional atmosphere were used as mediating variables to study the effects of challenge-hindrance stressors on innovation performance ( Kopelman et al, 1990 ; Hofmann and Stokburger-Sauer, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we have reached a consensus on the negative impact of hindrance stressors on innovation performance ( Baer et al, 2003 ; Ohly et al, 2006 ; Lin et al, 2015 ). Therefore, we set off from the conservation of resource theory, taking challenge stressors as a positive situation feature and hindrance stressors as a negative situation feature ( Baka and Prusik, 2021 ; Tong et al, 2021 ). At the same time, positive emotional atmosphere and negative emotional atmosphere were used as mediating variables to study the effects of challenge-hindrance stressors on innovation performance ( Kopelman et al, 1990 ; Hofmann and Stokburger-Sauer, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hindrance stressors have a negative effect on innovation performance, and its emotional and gradual blocking characteristic cannot be ignored ( Joseph and Ryan, 2019 ). Regardless of the extent of hindrance stressors, it will cause individual resource imbalance, and then lead to job burnout, emotional exhaustion, feedback avoidance, and performance deficiencies and other problems ( Baka and Prusik, 2021 ). The emotionality of blocking stressors pointed out, due to the time accumulation effect of employees’ perception of external things, when individuals’ pressure gradually increases and produces negative effects, the emotional nature of hindrance stressors ( Ramos and Mormède, 1998 ) will lead to negative work emotions such as job burnout, which will affect the completion of individual innovation work and innovation performance ( Ordóñez et al, 2016 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies conducted among nurses which applied JD-R theory confirmed that such stressors, as excessive workload ( 23 , 24 ) third-party aggression ( 23 , 25 ), emotional and organizational demands ( 26 , 27 ) are related to burnout among this professional group. However, the amount of research which used JD-R model to examine direct relationships as well as indirect via emotional labor between such fundamental stressors for nursing staff as organizational constraints and interpersonal conflict at work and burnout is scarce ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 86%
“…Baka and Prusik ( 24 ) indicated that currently researchers who apply JD-R model are looking for potential mediational variables that would deepen the understanding of mechanisms regulating the relationship between job demands and burnout. One of them is emotional labor which recently has been attracting attention as a factor that relates to burnout and turnover intention among nurses ( 43 ).…”
Section: Introductionmentioning
confidence: 99%